Saoul comme une bourrique ou comme un polonais? Boire: une réflexion phraséologique et traductologique (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
The present communication is focused on the phrasemes referring to the act of Phrasis Diciembre 2019 39 “drinking”. They will be analysed according to three perspectives: the lexicographic, linguistic and translational ones. The starting point of our analysis will be the lexicographic research carried out through the electronic edition of the Petit Robert in order to explore its « phraseological nomenclature » and finally constitute a corpus on an onomasiological basis. In the second phase of our study, lexicographic results will be compared with a sample of available and up-to-date corpora data in order to highlight some preliminary observations on the historical evolutions and discourse patterns characterising our selected phrasemes. The third and final step of our research will aim at recognizing the French-Italian phrasemes which can be defined as translational equivalents (Baker, 2011; Salmon, 2003; Delisle 2000). Their frequency inside corpora as well as their phraseological co-texts will be related to discourse patterns specific to our equivalents.
Keywords: phraseology; lexicography; translation studies; corpus analysis